1997
DOI: 10.1002/ana.410410409
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathological phenotype of the original family with Charcot‐Marie‐Tooth type 1B: A 20‐year study

Abstract: Charcot-Marie-Tooth type 1B is an uncommon form of hereditary motor and sensory neuropathy caused by mutations in the P(0) myelin protein gene on chromosome 1. We report here a 20-year observation of 13 members of the first family with Charcot-Marie-Tooth disease to demonstrate linkage to chromosome 1 and now known to have a C270A mutation in the P(0) gene altering the extracellular domain of the protein. Affected individuals generally show an early age at onset, often indicated by delayed ability to walk. Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
40
0
2

Year Published

1999
1999
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 29 publications
(14 reference statements)
4
40
0
2
Order By: Relevance
“…A similar finding was observed in an autopsy of a 92-year-old with CMT 1B. 8 CMT is primarily a peripheral nerve disease; however, our observations complement postmortem studies that suggest the pathology may extend to involve the central nervous system at least to the level of the spinal cord affecting both the anterior and posterior portions. It is unclear whether this is a primary process or secondary retrograde (anterior horn cells) and anterograde (posterior column) degeneration from the peripheral nerve disease.…”
supporting
confidence: 84%
See 2 more Smart Citations
“…A similar finding was observed in an autopsy of a 92-year-old with CMT 1B. 8 CMT is primarily a peripheral nerve disease; however, our observations complement postmortem studies that suggest the pathology may extend to involve the central nervous system at least to the level of the spinal cord affecting both the anterior and posterior portions. It is unclear whether this is a primary process or secondary retrograde (anterior horn cells) and anterograde (posterior column) degeneration from the peripheral nerve disease.…”
supporting
confidence: 84%
“…The temporal course of spinal cord involvement is also unclear. The association of spinal cord atrophy with specific types of CMT has yet to be elucidated, although available data suggest association with multiple types including CMT1B, CMT II, and HMSN V. [5][6][7][8] We speculate that the degree of spinal cord atrophy may affect clinical disease progression, as in our patient with spinal cord atrophy, who experienced a fast decline following many years of slow progression.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Demyelination, remyelination, inflammatory cell infiltration, and onion bulb formation have been found in spinal nerve roots in acute 18 and chronic 15,30,31,35 inflammatory demyelinating polyradiculoneuropathies. Demyelinative changes in both peripheral nerves and spinal nerve roots have also been reported in hypertrophic hereditary motor and sensory neuropathy, 4 protein zero-deficient mice, 9,26 peripheral myelin protein-22 deficient mice, 40 Trembler mice, 2 and Trembler-J mice 13 and in animal models of inflammatory demyelinating neuropathy. 1,14,17,24,38,39 In 2 mice with POEMS, which is a monoclonal plasma cell disorder characterized by polyneuropathy (P), organomegaly (O), endocrinopathy (E), monoclonal gammopathy (M), and skin changes (S), spinal nerve roots and sural nerves showed the same pathologic changes of demyelination, remyelination, and inflammatory cell infiltration, 42,47 and in 3 cases of diabetic neuropathy, there was severe loss of both large and small MF in sural nerves while segmental demyelination and remyelination was the main finding in both dorsal and ventral spinal roots.…”
Section: Discussionmentioning
confidence: 90%
“…This is likely to be determined by the site and nature of the mutation in the P0 gene. Interestingly, Bird et al 4 reported variability in severity within the same family, even though each affected person had the same mutation.…”
mentioning
confidence: 96%